2020
DOI: 10.1534/genetics.120.303613
|View full text |Cite
|
Sign up to set email alerts
|

An Opaque Cell-Specific Expression Program of Secreted Proteases and Transporters Allows Cell-Type Cooperation inCandida albicans

Abstract: An unusual feature of the opportunistic pathogen C. albicans is its ability to stochastically switch between two distinct, heritable cell types called white and opaque. Here, we show that only opaque cells, in response to environmental signals, massively up-regulate a specific group of secreted proteases and peptide transporters, allowing exceptionally efficient use of proteins as sources of nitrogen. We identify the specific proteases (members of the secreted aspartyl protease (SAP) family) needed for opaque … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Many virulence factors provide important functions required for the pathogenesis of C. albicans , such as morphogenesis (the transition between yeast and hyphae), white (W)/opaque (O) switching [24], secreted aspartic proteases (Saps) and adhesins [25]. Ten secreted aspartic proteases (Saps) have been identified in C. albicans , which are encoded by the SAP genes ( SAP1 to SAP10 ) [26] and associated with bovine serum albumin (BSA) utilisation [27]. It has been demonstrated that Saps are involved in protection from host defence proteins, biofilm formation and adhesion, among other functions [27].…”
Section: Introductionmentioning
confidence: 99%
“…Many virulence factors provide important functions required for the pathogenesis of C. albicans , such as morphogenesis (the transition between yeast and hyphae), white (W)/opaque (O) switching [24], secreted aspartic proteases (Saps) and adhesins [25]. Ten secreted aspartic proteases (Saps) have been identified in C. albicans , which are encoded by the SAP genes ( SAP1 to SAP10 ) [26] and associated with bovine serum albumin (BSA) utilisation [27]. It has been demonstrated that Saps are involved in protection from host defence proteins, biofilm formation and adhesion, among other functions [27].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that opaque cells are the mating competent cell type [ 21 ] and are less susceptible to phagocytosis by macrophages, potentially promoting immune evasion [ 24 , 46 ]. Our recent work has also shown that, due to a specialized secreted protease program, a small number of opaque cells can promote growth of a large white cell population; thus, the 2 cell types can act synergistically [ 47 ]. Aside from its physiological roles, white-opaque switching has many advantages as a eukaryotic system to study stochastic phenotypic switching.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has also shown that, due to a specialized secreted protease program, a small number of opaque cells can promote growth of a large white cell population; thus the two cell types can act synergistically (Lohse et al, 2020). Aside from its physiological roles, white-opaque switching has many advantages as a eukaryotic system to study stochastic phenotypic switching.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that opaque cells are the mating competent cell type (Miller & Johnson, 2002) and are less susceptible to phagocytosis by macrophages, potentially promoting immune evasion (Lohse & Johnson, 2008;Sasse et al, 2013). Recent work has also shown that, due to a specialized secreted protease program, a small number of opaque cells can promote growth of a large white cell population; thus the two cell types can act synergistically (Lohse et al, 2020). Aside from its physiological roles, white-opaque switching has many advantages as a eukaryotic system to study stochastic phenotypic switching.…”
Section: Discussionmentioning
confidence: 99%